Ion type and valency differentially drive vimentin tetramers into intermediate filaments or higher order assemblies. - Denz, Manuela; Marschall, Manuel; Herrmann, Harald; Koester, Sarah (Soft Matter, 2021)
Vimentin intermediate filaments, together with actin filaments and microtubules, constitute the cytoskeleton in cells of mesenchymal origin. The mechanical properties of the filaments themselves are encoded in their molecular architecture and depend on their ionic environment. It is thus of great interest to disentangle the influence of both the ion type and their concentration on vimentin assembly. We combine small angle X-ray scattering and fluorescence microscopy and show that vimentin in the presence of the monovalent ions, K+ and Na+, assembles into "standard filaments" with a radius of about 6 nm and 32 monomers per cross-section. In contrast, di- and multivalent ions, independent of type and valency, lead to the formation of thicker filaments associating over time into higher order structures. Hence, our results may indeed be of relevance for living cells, as local ion concentrations in the cytoplasm during certain physiological activities may differ considerably from average intracellular concentrations.
EVALuna2:417062